Deindustrialisation and the politics of subordinate degrowth: The case of Greater Buenos Aires, Argentina. (May 2023) - Schindler, Seth; Kanai, J Miguel; Diaz Bay, Javier
Cities in low- and middle-income countries have experienced deindustrialisation as localised agglomerations that historically served domestic and regional markets have become exposed to highly productive global value chains as capital has been (re)allocated to primary sectors. State, corporate and social actors have responded to economic decline by embracing a range of coping and adaptation strategies, some of which are consistent with degrowth, but they are often combined with business-as-usual initiatives in pursuit of economic growth. We refer to this as subordinate degrowth because localised responses are conditioned by the subordinate position of countries and cities in the global economy. While we acknowledge its divergence from 'pure' ideal-type degrowth, we do not dismiss the transformative potential of incremental change. Indeed, we argue that any realistic strategy to spatialise degrowth within cities must recognise the indeterminacy and messiness of urban politics. We employ subordinate degrowth as an analytic to interpret responses to deindustrialisation and economic decline in Buenos Aires, Argentina. Our analysis attends to three meso-level blind spots that characterise much degrowth scholarship, between (1) particular and universal, (2) advanced-industrial and agrarian ideal-types and (3) past/current socio-technical regimes and 'pure' degrowth.